2014
DOI: 10.1016/j.irfa.2013.12.005
|View full text |Cite
|
Sign up to set email alerts
|

On the linkages between stock prices and exchange rates: Evidence from the banking crisis of 2007–2010

Abstract: This study examines the nature of the linkages between stock market prices and exchange rates in six advanced economies, namely the US, the UK, Canada, Japan, the euro area, and Switzerland, using data on the banking crisis between 2007 and 2010. Bivariate UEDCC-GARCH models are estimated producing evidence of unidirectional Granger causality from stock returns to exchange rate changes in the US and the UK, in the opposite direction in Canada, and bidirectional causality in the euro area and Switzerland. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
79
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(94 citation statements)
references
References 62 publications
8
79
0
1
Order By: Relevance
“…Kanas (2000) documented volatility spillovers from stock market to EX market for all six industrial countries except Germany whereas no evidence was found of volatility spillovers in the opposite direction for any country. Furthermore, Caporale, Hunter, & Ali (2014) found causality in variance from stock returns to EX changes for US during 2007-2010 and in the opposite direction for the Euro area and Japan, while an evidence of bidirectional feedback was documented for Switzerland and Canada during the same period. Volatility spillover research carried on emerging stock and foreign exchange markets (e.g.…”
Section: Brief Literature Reviewmentioning
confidence: 91%
See 1 more Smart Citation
“…Kanas (2000) documented volatility spillovers from stock market to EX market for all six industrial countries except Germany whereas no evidence was found of volatility spillovers in the opposite direction for any country. Furthermore, Caporale, Hunter, & Ali (2014) found causality in variance from stock returns to EX changes for US during 2007-2010 and in the opposite direction for the Euro area and Japan, while an evidence of bidirectional feedback was documented for Switzerland and Canada during the same period. Volatility spillover research carried on emerging stock and foreign exchange markets (e.g.…”
Section: Brief Literature Reviewmentioning
confidence: 91%
“…Choudhry (2004); Morales (2008); and references cited in Kumar (2013)) gave similar results to those studies done on developed markets. MGARCH models have been employed to explore volatility spillovers between EX and equity markets (Caporale et al, 2014;Choudhry, 2004;Kanas, 2000;Kumar, 2013;Morales, 2008). Volatility transmission between financial markets could be examined using the two-step GARCH-VAR framework, whereby conditional volatility of financial variables is extracted from univariate GARCH models and, then, VAR model is used to test for causality between their conditional variances [e.g.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…This particular approach allows measurement of the dynamic interdependence between assets in the short run, assuming fast information flow between two major financial markets. The studies of Moore and Wang (2014) and Caporale et al (2014) also used DCC methodology to investigate the short-run interdependence between stocks and exchange rate. This model also allows measurement of long memory as well as asymmetric effect.…”
Section: Introductionmentioning
confidence: 99%
“…Empirically, some preliminary examinations using the correlation approach have revealed interdependence among higher-moment risks (e.g., Cooley, Roenfeldt, & Modani, 1977;Gupta & Chatiras, 2004). Recently, Caporale, Hunter, and Ali (2014) found evidence of causality-in-variance across stock and currency markets in advanced countries during the 2007-2010 crisis period. In our study, we support potential interdependence among higher-moment risks in both static (impulse response analysis) and dynamic (spillover index) approaches.…”
Section: Introductionmentioning
confidence: 99%